2014
DOI: 10.1007/s00018-013-1543-6
|View full text |Cite
|
Sign up to set email alerts
|

Yeast prions and human prion-like proteins: sequence features and prediction methods

Abstract: Prions are self-propagating infectious protein isoforms. A growing number of prions have been identified in yeast, each resulting from the conversion of soluble proteins into an insoluble amyloid form. These yeast prions have served as a powerful model system for studying the causes and consequences of prion aggregation. Remarkably, a number of human proteins containing prion-like domains, defined as domains with compositional similarity to yeast prion domains, have recently been linked to various human degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 117 publications
(189 reference statements)
0
48
0
Order By: Relevance
“…In particular, full-length Yck1 has been shown to stimulate [PSI + ] formation when overexpressed (42), suggesting that the fulllength protein may have some prion-like activity. Finally, regions outside of the Sup35 PFD can influence prion activity (12), so although we showed that a small number of mutations can confer prion activity on the Puf4 and YLR177W PrLDs, these domains may still not act as prions in their native context. Additionally, factors such as expression level, cellular localization, and binding partners likely all affect prion activity in ways that have not yet been fully defined.…”
Section: Discussionmentioning
confidence: 70%
“…In particular, full-length Yck1 has been shown to stimulate [PSI + ] formation when overexpressed (42), suggesting that the fulllength protein may have some prion-like activity. Finally, regions outside of the Sup35 PFD can influence prion activity (12), so although we showed that a small number of mutations can confer prion activity on the Puf4 and YLR177W PrLDs, these domains may still not act as prions in their native context. Additionally, factors such as expression level, cellular localization, and binding partners likely all affect prion activity in ways that have not yet been fully defined.…”
Section: Discussionmentioning
confidence: 70%
“…We next sought to test the hypothesis that phosphorylation could disrupt FUS self‐association and aggregation by altering the biophysical properties of the LC. One measure of the self‐assembly/aggregation propensity of disordered domains is a quantitative assessment of their “prion‐like” character, a name given to sequences enriched in polar residues and lacking charged and aliphatic residues as found in yeast prion proteins (Cascarina & Ross, 2014). Mimicking phosphorylation at S/TQ positions by substitution of serine or threonine with the negatively charged residue glutamic acid (glutamate) results in a marked decrease in the prion‐like propensity as measured by the PLAAC algorithm (Fig 1A; Lancaster et al , 2014), which identifies probable prion‐like protein segments.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 These properties have been used to help identify several other prions in S. cerevisiae although it is very likely that many others exist. 48,51 It is worth pointing out that, in addition to the effect of Reed Wickner's 1994 paper on the direction of [PSI C ] prion studies, it "changed the water on the beans" for prion biology in a more general way. As we note above, we think it is fair to say that acceptance of Stanley Prusiner's prion hypothesis had until then been grudging, in spite of papers from his laboratory and others illuminating the molecular basis of spongiform encephalopathies.…”
Section: Confirming [Psi C ] Is a Transmissible Amyloidmentioning
confidence: 99%